2017
DOI: 10.1002/adhm.201700030
|View full text |Cite
|
Sign up to set email alerts
|

Damage, Healing, and Remodeling in Optogenetic Skeletal Muscle Bioactuators

Abstract: A deeper understanding of biological materials and the design principles that govern them, combined with the enabling technology of 3D printing, has given rise to the idea of "building with biology." Using these materials and tools, bio-hybrid robots or bio-bots, which adaptively sense and respond to their environment, can be manufactured. Skeletal muscle bioactuators are developed to power these bio-bots, and an approach is presented to make them dynamically responsive to changing environmental loads and robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 44 publications
0
65
0
Order By: Relevance
“…These biobots could actuate in a specified direction at high speeds up to the speed of 156 µm/s under bipolar electrical pulses (Figure b). Raman et al further modified the design to enable optical stimulation with blue light by using optogenetically modified C2C12 murine myoblast cells …”
Section: Applicationsmentioning
confidence: 99%
“…These biobots could actuate in a specified direction at high speeds up to the speed of 156 µm/s under bipolar electrical pulses (Figure b). Raman et al further modified the design to enable optical stimulation with blue light by using optogenetically modified C2C12 murine myoblast cells …”
Section: Applicationsmentioning
confidence: 99%
“…Over the past few decades, considerable progress has been made in developing various effective biohybrid actuators, including actuation strategies based on bacteria, motile cells, whole‐muscle tissues, engineered skeletal muscle tissues, and cardiomyocytes . These biohybrid robotics present a promising potential to provide artificial devices with the ability to take advantage of the unique features of biological systems, such as self‐heal ability when subjected to damage; inexpensive and easily available fuel sources (mostly sugars and fatty acids); eco‐friendly during the fuel‐work conversion and silent operation . Among all the reported biohybrid actuators, cardiomyocyte‐based systems exhibit incomparable advantages with much better stroke and stress than other kinds .…”
Section: Discussionmentioning
confidence: 99%
“…To test the hypothesis that biointegrated materials can mimic the complex functional behaviors observed in natural biological systems, we studied the effect of induced damage to engineered muscle and developed a protocol to completely heal the tissue within two days. By mimicking the wound healing process observed in vivo, we showed that a combination of undifferentiated myoblasts, localized secretion of growth factors, and exercise‐driven remodeling could yield recovery of bioactuator form and function, a capability that had not previously been demonstrated in any synthetic actuator …”
Section: Responsive Biointegrated Hydrogelsmentioning
confidence: 91%